2017
DOI: 10.3389/feduc.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

A Competency Model of Psychology Practice: Articulating Complex Skills and Practices

Abstract: As in all professions, the practice of psychologists is based on the acquisition and application of knowledge, skills, and behaviors that are often conceptualized as competencies. As students progress through their curricula, they might approach each individual unit as a discrete set of skills embedded in different coursework units. However, these discrete skills and competencies may not reflect the diverse, interrelated, and complex nature of the practice of psychology. This project sought to identify the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…While there was no assessment in this study of whether the exercise led to an increase in self-reflective capacity, the SR component did enable observation of the trainees' ability to self-assess for the development of their professional skills. Such selfassessment and reflection has previously been described as a meta-competency that is central to practitioners' ongoing development (Thwaites et al, 2014;Thwaites et al, 2015;von Treuer and Reynolds, 2017). As an assessment task, the exercise also allowed for the provision of private, individually tailored feedback on the participant's progress in developing these skills.…”
Section: Sp/sr As a Form Of Competency-based Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While there was no assessment in this study of whether the exercise led to an increase in self-reflective capacity, the SR component did enable observation of the trainees' ability to self-assess for the development of their professional skills. Such selfassessment and reflection has previously been described as a meta-competency that is central to practitioners' ongoing development (Thwaites et al, 2014;Thwaites et al, 2015;von Treuer and Reynolds, 2017). As an assessment task, the exercise also allowed for the provision of private, individually tailored feedback on the participant's progress in developing these skills.…”
Section: Sp/sr As a Form Of Competency-based Assessmentmentioning
confidence: 99%
“…This is yet to be discussed in the SP/SR literature. It has previously been identified that psychological practice involves competencies relating to the assessment of client needs, the ability to design evidence-based interventions, the ability to implement interventions, and the ability to evaluate outcomes of these (von Treuer and Reynolds, 2017). SP/SR includes the formulation of the trainee's own problems, the application of interventions to these problems, and a reflection on what is learned from the exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Competence involves understanding and performing tasks consistent with one's professional qualifications anchored to EBP (APA, ). SP competence has been defined as a trainee's ability to demonstrate knowledge of theoretical and research evidence related to diagnosis, assessment, and psychological intervention (Gonsalvez et al, ; von Treuer & Reynolds, ). Gonsalvez et al () conceptualise the SP mindset as a meta competency comprising knowledge, skills, and attitudinal elements directed towards evidence and respect for the scientific method in practice (see competency benchmarks; APA, ; von Treuer & Reynolds, ).…”
Section: Competency‐based Approaches and The Sp Competencymentioning
confidence: 99%
“…Accurate and reliable measurement of early supervision and trainee competence is crucial to the objective evaluation of specific competencies and trainee performance (Gonsalvez & McLeod, 2008;Gonsalvez, Oades, & Freestone, 2002;Nicholson-Perry, Donovan, Knight, & Shires, 2017;Rodolfa et al, 2014;von Treuer & Reynolds, 2017). Further to this, comparison of supervisor and supervisee perceptions of supervision to determine which factors contribute to concordance and discordance in supervisory dyads regarding competency ratings and learning outcomes would be useful.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The popularity of sports psychology has grown substantially in the past two decades, and the importance of being mentally prepared prior to an athletic competition is now well-documented (von Treuer and Reynolds, 2017). Historically, sports psychology came about through the specific intention to enhance performance, but over time, the need to focus on athlete wellbeing as an integral part of performance has come sharply into focus (Sebbens et al, 2016).…”
Section: Linking Performance and Wellbeing: Directions In Sportsmentioning
confidence: 99%